“I Like it Clean”: Brazilian Waxing and Postfeminist Subjectivity Among South Asian Beauticians in London - Dutta, Nandita (Frontiers in Sociology, 2021)
Postfeminism is a neoliberal sensibility that locates femininity in the body, thereby imploring women to constantly labour on, monitor and discipline their bodies. This aesthetic labour is presented to women as freely chosen and empowering. Brazilian waxing is exemplary aesthetic labour directed at the self. Academic literature on aesthetic labour in general, and Brazilian waxing in particular, looks at white and middle-class women, as this category of women is considered the putative subject of postfeminism. Little attention is paid to racialised women from the global south who perform aesthetic labour on other women’s bodies in the global north. In this paper, I draw on my ethnographic study of two beauty salons in London run by South Asian women to argue that these South Asian beauticians are postfeminist subjects as well. The aim of challenging the putative subject of postfeminism, using the example of Brazilian waxing, is not merely to include South Asian women in the discourse, but to advance a transnational theorisation of postfeminism. Such theorisation, I demonstrate, leads to a better understanding of how postfeminism is implicated in global structures of power as well as the affective qualities of postfeminism including intimacy and disgust.